2014
DOI: 10.1007/s00535-014-0964-9
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle depletion is an independent prognostic factor for hepatocellular carcinoma

Abstract: Skeletal muscle depletion is an independent prognostic factor. Intervention to prevent muscle wasting might be an effective strategy for improving the outcome of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
191
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(223 citation statements)
references
References 36 publications
16
191
2
2
Order By: Relevance
“…Sarcopenia and myosteatosis have been significantly associated with a range of adverse outcomes including increased rate of post‐operative complications,10, 11, 40, 41, 42 longer length of hospital stay,41, 43 30‐day post‐operative mortality and in‐hospital mortality,44 and dose‐limiting toxicities 5, 6, 7, 8, 45, 46, 47, 48, 49, 50. In addition, the conditions have been demonstrated as independent predictors of reduced overall survival 18, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64. The situation is further complicated by the obesity epidemic that has been progressively worsening in recent times.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia and myosteatosis have been significantly associated with a range of adverse outcomes including increased rate of post‐operative complications,10, 11, 40, 41, 42 longer length of hospital stay,41, 43 30‐day post‐operative mortality and in‐hospital mortality,44 and dose‐limiting toxicities 5, 6, 7, 8, 45, 46, 47, 48, 49, 50. In addition, the conditions have been demonstrated as independent predictors of reduced overall survival 18, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64. The situation is further complicated by the obesity epidemic that has been progressively worsening in recent times.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of the CT-CSA at L3 is reliable for the assessment of sarcopenia [11, 17]. Hepatocellular carcinoma patients with sarcopenia defined by the CT-CSA measurement have a significantly higher mortality than those without sarcopenia [18]. Among patients treated with capecitabine for metastatic breast cancer, those with sarcopenia defined by the CT-CSA have a higher grade of chemotherapy toxicity and a shorter time to disease progression than those without sarcopenia [19].…”
Section: Discussionmentioning
confidence: 99%
“…The crude pooled HR of skeletal muscle mass loss for recurrence-free survival from 6 studies was calculated to be 1.85 (95% CI: 1.44-2.37) [21,22,24,[26][27][28], while the adjusted summary HR from 4 selected trials was 1.76 (95% CI: 1.27-2.45) (Fig. 5) [22,23,26,27].…”
Section: Recurrence-free Survivalmentioning
confidence: 99%
“…In terms of patient demographic characteristics, female patients accounted for 28.4% of the investigated population and the mean (or median) age of the enrolled patients in each study (or its subgroup) ranged between 57 and 73.9 years. Regarding the pattern of underlying malignancy, 7 studies included patients with resectable HCC [21][22][23][24][25][26][27], 3 included patients with any clinical stage of HCC [20,28,29], 1 included patients with primary liver tumors (69.8% had HCC) [30], 1 included patients with hepatic cancers (50.5% had HCC) undergoing intraarterial therapy [31], and 1 included patients with HCC following sorafenib treatment [32]. The muscle volume was estimated on the transverse CT image at the third lumbar vertebra level in all the selected studies, although the intensity window -(shown by using the Hounsfield scale) for recognizing skeletal muscles and cut-off points for sarcopenia -varied across trials ( Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%